Pengetahuan Gizi Seimbang Terhadap Perilaku Pemilihan Makanan Jajanan Pada Remaja di SMK Kesehatan Bali Khresna Medika - Ni Putu Eny Sulistyadewi; Rai Riska Resty Wasita (Politeknik Negeri Jember, 2022)
Nutritional problems in adolescents must receive special attention because they will affect the growth and development of their bodies and can have an impact on nutritional problems as adults. Knowledge of balanced nutrition in adolescents is an important key in choosing nutritious and safe foods so that they can support their health. The purpose of this study was to determine the effect of knowledge of balanced nutrition on the behavior of choosing snacks in adolescents. This study uses a quantitative descriptive method with a cross-sectional design. This research will be carried out at the Bali Khresna Medika Health Vocational School from September – to December 2021. The research sample is teenagers aged 15-18 years as many as 114 people who are determined based on purposive sampling. Data collection was carried out using a balanced nutrition knowledge questionnaire and snack food selection behavior in adolescents. The data were statistically analyzed using the chi-square test with SPSS. The results showed that most of the research subjects had knowledge of balanced nutrition in the good category (58.8%), knowledge of the selection of snacks in the less category (50.9%), attitudes in the selection of snacks in the less category (60.5%), actions/practices in the selection of snacks in the good category (64%), and behavior in the selection of snacks as a whole in the good category (53.5%). Based on statistical tests, it is known that there is no relationship between knowledge of balanced nutrition on the behavior of choosing snacks in adolescents p > 0.05